2017
DOI: 10.4149/gpb_2017039
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic regulation of brain catecholamine neurotransmission: In vivo electrophysiology and microdialysis study in rats

Abstract: Abstract. It was previously reported that adenosine-2A (A 2A ) receptors interact with dopamine-2 (D 2 ) receptors on a molecular level. The aim of the current study was to investigate the functional output of this interaction. In vivo microdialysis was used to assess the effects of an antagonist of A 2A receptors, ZM 241385, and an antagonist of D 2 receptors haloperidol, either alone or in combination, on brain catecholamine levels. It was found that ZM 241385 did not alter catecholamine levels by its own, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Norepinephrine neurons were recorded from the locus coeruleus (LC), 8.0–8.3 mm posterior to bregma, 1.2–1.4 mm lateral to the midline, and 5.5–7.5 mm ventral to the brain surface [26]. Norepinephrine neurons were recognized by regular firing rate of 0.5–5.0 Hz, positive action potential of long duration of 0.8–1.2 msec and a characteristic burst discharge in response to nociceptive pinch of the contralateral hind paw, as described in our previous studies [32,46,47,48]. After a norepinephrine neuron was identified and its basal firing activity was recorded for 2 min, SMe1EC2M3 was administered intravenously (i.v.)…”
Section: Methodsmentioning
confidence: 95%
“…Norepinephrine neurons were recorded from the locus coeruleus (LC), 8.0–8.3 mm posterior to bregma, 1.2–1.4 mm lateral to the midline, and 5.5–7.5 mm ventral to the brain surface [26]. Norepinephrine neurons were recognized by regular firing rate of 0.5–5.0 Hz, positive action potential of long duration of 0.8–1.2 msec and a characteristic burst discharge in response to nociceptive pinch of the contralateral hind paw, as described in our previous studies [32,46,47,48]. After a norepinephrine neuron was identified and its basal firing activity was recorded for 2 min, SMe1EC2M3 was administered intravenously (i.v.)…”
Section: Methodsmentioning
confidence: 95%
“…In fact, we observed that the selective A 2A R antagonist SCH58261 attenuated the D 2 R‐mediated inhibition of glutamatergic transmission in the PFC. Likewise, this inhibitory effect of dopamine was also reduced upon genetic deletion of A 2A R. This electrophysiological evidence is in notable agreement with a previous microdialysis study reporting an ability of A 2A R antagonists to attenuate D 2 R‐mediated effects in the PFC (Dremencov et al ., ). Our combined neurochemical evidence, identifying the co‐localization of A 2A R and D 2 R in glutamatergic nerve terminals (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, A 2A R can synergize with D 1 R in the hippocampus to control memory performance (Tyebji et al ., ). However, despite their parallel ability to control PFC‐dependent behavioural responses, the potential interplay between A 2A R and dopamine receptors has been seldom explored in the PFC (Pardo et al ., ; Dremencov et al ., ). Thus, we now tested whether the pharmacological or genetic manipulation of A 2A R affects the ability of dopamine to control glutamatergic synaptic transmission in the PFC.…”
Section: Introductionmentioning
confidence: 97%
“…Although the HPLC technique used in our study had been previously used [33, 43], it is important to consider that the degradation of DA and NE can occur from 200 to 2000 milliseconds [52], which made their measurement difficult. So, measurements by in vivo microanalysis may provide more reliable results [60].…”
Section: Discussionmentioning
confidence: 99%